Turns vs consensus: Learning mathematics in multi-touch surfaces. Issue 140 (August 2020) - Bacelo, Adrián; Roldán-Álvarez, David; Martín, Estefanía
Highlights: There is no significant difference between turns and consensus. Consensus methodology enhaces 21st century skills. There is no gender gap. Multi-touch table have a positive impact in the knowledge. Abstract: The adoption of information and communication technologies in primary education is crucial for adapting traditional classrooms to the digital era. Over time, young children are increasingly using touch screen technologies such as tablets at home and interactive whiteboards at school, either for leisure or for academic activities. However, the literature shows that there is still a gap between what is known about the benefits of using this technology and its real use in primary education settings. Most researchers have focused on the pedagogical theory behind using touch screen devices, but there are few empirical studies about how these technologies and different approaches affect students' learning processes. This paper presents two learning experiences in a primary school in Fuenlabrada (Madrid-Spain) where primary students performed mathematics activities using a multi-touch table with two different methodologies: turns and consensus. The results show that both methodologies help students acquire meaningful learning, but there is no statistically significance between them.